Transparent reporting in forensic Science: Exploring its meaning and challenges - Kristy A. Martire (Forensic Science International: Synergy)
The forensic and scientific communities widely endorse transparency as a core principle and fundamental obligation of forensic science reporting. Yet the definition of transparency - ironically – remains opaque. This ambiguity impacts scientist's ability to fulfill their obligations when reporting forensic findings to justice systems as the primary consumer. Applying Elliott's 2022 taxonomy of transparency clarifies the issue, revealing that transparency is central to achieving Reliability, Assessment, Justice, Accountability and Innovation goals. It involves disclosing information about the scientists' Authority, Compliance, Basis, Justification, Validity, Disagreements, and Context, and shows that the audiences for these disclosures includes not only primary consumers, but also a range of agents, actors, and stakeholders. This complexity creates a multidimensional challenge for scientists and forensic science service providers, requiring a careful balance between competing demands. Templates can mitigate some of these challenges, but must be coupled with ongoing collaboration among forensic scientists, legal stakeholders, and institutional bodies to ensure that reporting practices evolve in line with professional obligations, scientific rigor and the realities of forensic practice.